Detecção rápida de resistência a pirazinamida em Mycobcaterium tuberculosis pelo método em microplaca utilizando resazurina (REMA - Resazurin Microtiter Assay) - Campanerut, Paula Aline Zanetti (2010)
Tuberculosis (TB) is a chronic disease caused by an Acid Fast bacilli belonging to the Mycobacterium tuberculosis complex. Despite having almost been eradicated in developed countries, TB remains a major public health problem, especially in developing countries. Pyrazinamide (PZA) is a pro-drug used to treat TB, which requires conversion to its active form, pirazinóico acid (POA), by the pyrazinamidase enzyme (PZase), encoded by the pncA gene. Although the mechanism of action of POA remains unknown, it has been suggested that their accumulation in acidic pH, can disrupt the membrane potential of the bacillus, affecting the transport of nutrients. Early detection of drug resistance is very important for TB control and the beginning of treatment. However, the proportion method in Lowenstein-Jensen (LJ), that is routinely used in Brazil for detecting resistance in M. tuberculosis is laborious, time consuming and have low reproducibility at acid pH that is necessary to perform the test with PZA. Thus, the purpose of this study was standardize and evaluate the use of resazurin microtiter assay plate (REMA) for detection of resistant to PZA in M. tuberculosis. The research resulted the article: "Application of the resazurin microtiter assay plate (REMA) for detection of resistance in Mycobacterium tuberculosis", that shows how the REMA proposal may contribute to the rapid detection of PZA resistance, in a fast, sensitive and specific method.